Pengaruh Motivasi dan Dukungan Sosial terhadap Hasil Belajar Mata Pelajaran IPS pada Peserta Didik Kelas VIII di SMP Negeri 2 Sawan - Mesry Angelia Butarbutar; I Putu Arya Dharmayasa (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the effect of motivation and social support on learning outcomes of social studies subjects in class VIII students at SMP Negeri 2 Sawan. This type of research is causal quantitative. The sampling technique used a Likert scale instrument, the sempel in this study were VIII grade students of SMP Negeri 2 Sawan with a total sempel of 299 students. Data obtained from interviews, questionnaires, and documentation regarding learning motivation and social support as well as from document data on social studies learning outcomes of VIII grade students of SMP Negeri 2 Sawan. Data collection methods used are the results of interviews, questionnaires or questionnaires in the form of scale scores, and documentation. Based on the results of data analysis concluded that: (1) learning motivation of students in the good and very good category as much as 47.057 (2) social support of students in the good and very good category as much as 0.312% (3) Together and separately learning motivation and social support affect learning outcomes. So it can be concluded that the motivation variable (X1) has an influence on learning outcomes (Y). The positive T value indicates that the Motivation variable (X) has a significant positive effect on learning outcomes (Y), so the hypothesis in the study is accepted.